FORGIVENESS AND RESILIENCE: A CASE OF ADOLESCENTS WITH BROKEN HOME DIVORCE - Lestari, Tut Wuri Tri; Huwae, Arthur (Counsenesia Indonesian Journal Of Guidance and Counseling, 2023)
Discordant or unstable family conditions, such as difficult adjustment methods, aggressive behavior, and juvenile delinquency, are determining factors in the development of an unhealthy child's (adolescent) personality. Adolescents whose parents have both divorced (broken home) find it difficult to forgive the circumstances they are in; they are also sometimes unable to adapt after experiencing these painful conditions. The aim of this research was to see if there was a correlation between adolescents’ forgiveness and resilience in broken home divorce. This study employed a quantitative method with a correlational design. A total of 216 broken home adolescents aged 15 to 19 years old participated in this study, recruited by using a purposive sampling technique. The psychological scales Transregression Related Interpersonal Motivation 18 Version Loading Factors (a = 0.872) and The Resiliency Attitudes and Skills Profile (a = 0.937) were used in this study. The study's findings reveal a significant positive correlation between forgiveness and resilience in divorced adolescents from broken homes (r = 0.200 with sig = 0.002 (p<0.01)). Furthermore, forgiveness has an effective contribution of 4% (r2), and it is one of the factors associated with increased resilience, particularly for broken home divorce adolescents. In this case, the researchers see that broken home divorce adolescents have a moderate category of forgiveness and resilience. This study can serve as a basis for broken home persons, particularly adolescents, to forgive and recover from traumatic experiences such as broken homes.